1996
DOI: 10.1074/jbc.271.33.19991
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structure and Function of the Tachykinin Neurokinin-2 Receptor through Biosynthetic Incorporation of Fluorescent Amino Acids at Specific Sites

Abstract: A general method for understanding the mechanisms of ligand recognition and activation of G protein-coupled receptors has been developed. A study of ligandreceptor interactions in the prototypic seven-transmembrane neurokinin-2 receptor (NK2) using this fluorescence-based approach is presented. A fluorescent unnatural amino acid was introduced at known sites into NK2 by suppression of UAG nonsense codons with the aid of a chemically misacylated synthetic tRNA specifically designed for the incorporation of unna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 39 publications
3
114
0
Order By: Relevance
“…Given the broad range of structures and activities for GPCRs, as well as their undeniable pharmaceutical importance, it has been appreciated for some time that unnatural amino acids could provide a valuable probe of this essential class of membrane receptors. An early study incorporated the fluorescent unnatural amino acid NBD-Dap into the NK2 receptor and showed that exposure to tachykinin did produce measurable electrophysiological currents in Xenopus oocytes (due to opening of Ca 2ϩ -activated Cl Ϫ channels that are endogenous to the oocyte) (29). A very recent study used an orthogonal tRNAsynthetase pair to incorporate a benzophenone-containing unnatural amino acid into the Ste2p GPCR (30) and the CCR5 receptor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Given the broad range of structures and activities for GPCRs, as well as their undeniable pharmaceutical importance, it has been appreciated for some time that unnatural amino acids could provide a valuable probe of this essential class of membrane receptors. An early study incorporated the fluorescent unnatural amino acid NBD-Dap into the NK2 receptor and showed that exposure to tachykinin did produce measurable electrophysiological currents in Xenopus oocytes (due to opening of Ca 2ϩ -activated Cl Ϫ channels that are endogenous to the oocyte) (29). A very recent study used an orthogonal tRNAsynthetase pair to incorporate a benzophenone-containing unnatural amino acid into the Ste2p GPCR (30) and the CCR5 receptor (31).…”
Section: Discussionmentioning
confidence: 99%
“…This codon can be used in combination with the appropriate tRNA to introduce non-natural amino acids at the position of interest and does not require the deletion of other amino acids. Until now, only one publication has used this technique for fluorescence resonance energy transfer studies at a GPCR, the NK2 receptor (Turcatti et al, 1996). The limitations of the technique were due to the difficulties in producing large amounts of chemically aminoacylated suppressor tRNA that needs to be injected into large numbers of cells to produce significant amounts of protein.…”
Section: B Principles and Methods Of Resonance Energy Transfer Technmentioning
confidence: 99%
“…First, one can study the interaction between ligand and receptor as the FRET TECHNIQUES FOR GPCR ACTIVATION AND SIGNALING initial step in the signaling cascade (Turcatti et al, 1996;Castro et al, 2005). Second, FRET between two different labeled receptor-bound fluorescent ligands has been used to detect oligomeric GPCR complexes, not only in transfected cells but also in native tissue (Albizu et al, 2010).…”
Section: Ligand Binding To G-protein-coupled Receptorsmentioning
confidence: 99%
“…Highly sensitive measurements of unique channel activities made the absolute expression yield non-critical, with single cell expression being sufficient. However, these and other studies (26) have been mostly limited to oocytes. The low yield and the technical difficulties to produce and deliver chemically aminoacylated suppressor tRNA into a large number of mammalian cells made this method impractical for general studies of GPCRs.…”
mentioning
confidence: 99%